Physical oceanography during RV SONNE cruise SO263 - Lukas Klose; Charlotte Kleint; Andreas Türke; Karsten M Haase (PANGAEA, 2022)
This expedition was conducted in the North Eastern Lau Basin, Southwest Pacific. The program aimed at improving our understanding of the igneous, hydrothermal, and tectonic processes that occur during island arc and back-arc formation. Cruise SO263 operated in June 2018. Raw data of physical oceanography was obtained during research cruise SO263 on RV SONNE. Data of vertical CTD casts was binned to 1 meter intervals and is reported with shortend header. Data of tow-yo CTD casts was binned to 1 second intervals and is reported with shortend header.